2019
DOI: 10.1161/circresaha.118.313316
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Tuning of Sox17 and Canonical Wnt Coordinates the Permeability Properties of the Blood-Brain Barrier

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
72
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(79 citation statements)
references
References 31 publications
2
72
0
Order By: Relevance
“…While these factors and their direct responders LRP5 and LRP6 are significantly reduced in the acute phase, they show an induction 7 days after tMCAO. This finding is of special interest as Wnt/β-catenin signaling has recently been shown to conduct its crucial role in brain angiogenesis and BBB formation at the NVU (Liebner et al, 2008;Reis et al, 2012) potentially via SOX17 induction (Corada et al, 2018). Furthermore, pharmacological induction of β-Catenin by CHIR99021 was able to reactivate matured cardiomyocytes and therefore suggested as a future approach for regeneration after myocardial infarction (Fan et al, 2018).…”
Section: Discussionmentioning
confidence: 93%
“…While these factors and their direct responders LRP5 and LRP6 are significantly reduced in the acute phase, they show an induction 7 days after tMCAO. This finding is of special interest as Wnt/β-catenin signaling has recently been shown to conduct its crucial role in brain angiogenesis and BBB formation at the NVU (Liebner et al, 2008;Reis et al, 2012) potentially via SOX17 induction (Corada et al, 2018). Furthermore, pharmacological induction of β-Catenin by CHIR99021 was able to reactivate matured cardiomyocytes and therefore suggested as a future approach for regeneration after myocardial infarction (Fan et al, 2018).…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, noncanonical Wnt signaling may contribute to the establishment of the BBB phenotype (Pinzón-Daza et al, 2014). Sox17 has been identified as a major target of the β-catenin pathway in endothelial cells (Corada et al, 2019), together with Lef1 and Ets1 (Roudnicky et al, 2020). These Wnt-regulated transcription factors up-regulate the transcription of several junctional proteins, including VE-cadherin and claudin-5 (Roudnicky et al, 2020), possibly involved in the repair of the BSCB.…”
Section: Discussionmentioning
confidence: 99%
“…Forebrain angiogenesis in the mouse was traditionally thought to begin at E10.0-E11.5, to peak around birth and then to gradually decline until postnatal day 25 (P25) when the vascular network becomes functionally mature and quiescent (reviewed by Engelhardt and Liebner, 2014). However, recent RNA sequencing studies suggest the existence of a second wave of postnatal brain angiogenesis that has not been appreciated in previous studies (Corada et al, 2019;Hupe et al, 2017). These studies have shown that endothelial cell-specific mRNA transcripts encoding:…”
Section: Bbb/brb Integrity Depends On Proper Nvu Assembly and Organizmentioning
confidence: 99%
“…(3) cell proliferation markers; or (4) cell cycle markers are decreased between E15.5 and E18.5 in the forebrain when compared with E11.5-E13.5, but exhibit a rapid increase in levels during the first week after birth (P5 and P9), indicative of a potential second wave of angiogenesis (Corada et al, 2019;Hupe et al, 2017). These molecular studies are supported by analyses of endothelial cell proliferation (e.g.…”
Section: Bbb/brb Integrity Depends On Proper Nvu Assembly and Organizmentioning
confidence: 99%